Marginal External Costs of Peak and Non Peak Urban Transport in Belgium - Leo De Nocker; Stef Vergote; Luc Vinckx; Guido Wouters (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper discusses intermediate results of an ongoing research project to estimate all external costs from all transport modes in Belgium. It gives estimates of the marginal external costs of air pollution from urban transport. The evaluation of the environmental impacts is based on the European ExternE accounting framework. This methodology uses the impact pathway analysis for the detailed bottom-up assessment of impacts from air pollutants. It integrates state of the art knowledge in the fields of emission modelling, dispersion modelling, dose-response functions and monetary valuation. This paper focuses on the impact of location (rural areas versus cities), regulation, traffic conditions and congestion on environmental externalities. These case studies for Belgium confirm earlier results of the ExternE project that external environmental costs of car transport are significant and that damage to public health is the dominant impact. In addition, it shows that externalities of urban peak traffic are 2 to 4 times higher than for normal urban driving conditions. Finally, it calculates which occupancy rates are required for urban public transport (trams and diesel buses) to have lower external costs compared to passenger cars.
Keywords: H43; I31; R49; Q30; Q49; 330; Externalities; Urban transport; Air pollution; Congestion; Sustainable mobility